2014
DOI: 10.1556/avet.2014.023
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 7- (IRF7-) mediated immune response affects Newcastle disease virus replication in chicken embryo fibroblasts

Abstract: Interferon regulatory factor 7 (IRF7) is essential for the induction of an antiviral response. Previous studies have shown that virus replication causes the activation or expression of Type I interferon (IFN) in cells, which further activates IFN-stimulated genes (ISGs) to retard virus growth. In this study, after infection of chicken embryo fibroblasts (CEFs) with the lentogenic Newcastle disease virus (NDV) strain LaSota or the velogenic NDV strain GM, the mRNA and protein levels of IRF7 showed a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…Specifically, IL-1β was highly expressed in the lungs and glandular stomach, which are important target organs of NDV, in chickens infected with the virulent strain compared to those infected with the attenuated virus. Moreover, when infected at a MOI of 1, GM NDV induced higher levels of IL-1β than those induced by the La Sota virus in a time-dependent manner, which is consistent with the results of previous studies [47]. Furthermore, as previously noted, treatment of chickens with anti-IL-1β antibodies following infection with GM NDV decreased IL-1β level in organs, reduced body temperature and decreased the mortality rate, further confirming an essential role for IL-1β in the virulence of NDV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, IL-1β was highly expressed in the lungs and glandular stomach, which are important target organs of NDV, in chickens infected with the virulent strain compared to those infected with the attenuated virus. Moreover, when infected at a MOI of 1, GM NDV induced higher levels of IL-1β than those induced by the La Sota virus in a time-dependent manner, which is consistent with the results of previous studies [47]. Furthermore, as previously noted, treatment of chickens with anti-IL-1β antibodies following infection with GM NDV decreased IL-1β level in organs, reduced body temperature and decreased the mortality rate, further confirming an essential role for IL-1β in the virulence of NDV infection.…”
Section: Discussionsupporting
confidence: 92%
“…The expressions of crucial genes, including TLR3, TLR7, IL1B, IRF7, IL8, STAT1, and MHC class I and II molecules, are characteristic of NDV infection in chicken cells. However, in previously performed studies, a significant expression of type I IFNs (INF-α and IFN-β) was observed against NDV infection [53,54]. Surprisingly, in our experimental settings, we were unable to observe this response.…”
Section: Discussioncontrasting
confidence: 80%
“…Major genes including IL1β, IL6, IL8, CCL4, CCL5, STAT1, TLR3, IRF7, IFITM-1, IFITM-3, IFITM-5, STAT1, NF-kB, MX1, RSAD2 (viperin), MDA5, and ZAP were identified in this study ( Supplementary Table S1). Interestingly, among all those crucial genes related to innate immunity identified in the present study, we found that TLR3, TLR7, IL1B, IRF7, IL8, STAT1, and MHC class I and II molecules are exactly the same as those observed in previously studies where similar gene expression was shown in CEFs treated with NDV (genotype VII and IX) [53,54]. In short, our results demonstrated a low level (nonsignificant) expression of IFN-α and IFN-β.…”
Section: Kegg Pathway Enrichmentsupporting
confidence: 89%
“…In our previous study using stable IRF7 overexpression and knockdown in chicken DF-1 cell lines with double-stranded RNA (dsRNA) analog poly(I:C) (polyinosinic-polycytidylic acid) inductions, we demonstrated the conserved function of IRF7 as a type I IFN modulator [14]. Another study also suggested a similar role of IRF7 by the siRNA knockdown of IRF7 in chicken embryonic fibroblasts (CEFs), which limited IFNA, IFNB and STAT1 (signal transducer and activator of transcription 1) expression and increased Newcastle disease virus replication [15]. While these knockdown approaches such as RNA interference (RNAi) have successfully generated partial IRF7 loss-of-function phenotypes in chickens, and generated some novel insights into the role of IRF7 in the regulation of the host response to virus infection in poultry, RNAi has its own technical limitation of incompleteness of knockouts [16].…”
Section: Introductionmentioning
confidence: 81%